Characterisation and Performance of Pindan Soils Modified with Polymer Stabilisers - Park, Hyun Kyu (Curtin University, 2018)
Moisture susceptibility of materials is an important aspect when pavements are designed as moisture can weaken bonds between aggregates. Pindan is a red soil, known as a moisture sensitive soil. This project focuses on fundamental information of Pindan soil and its improved performances using polymer stabilisers, then determines the chemical and physical bonding mechanisms associated with the polymer stabilisers. Chemical and microstructural properties were examined and linked with the mechanical properties.